EDUKASI PEMANFAATAN TEKNOLOGI KECERDASAN BUATAN UNTUK PERLINDUNGAN DATA PRIBADI DI KELURAHAN DURI KEPA KEBON JERUK JAKARTA BARAT - Roy Mubarak; Waseso, Bayu (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
In the current digital era, the protection of personal data has become a crucial issue that continues to face various challenges. The increasing number of data breach incidents poses a potential risk for the misuse of personal information, while public awareness regarding the importance of data protection remains relatively low. Many individuals easily share their personal data without understanding the potential risks involved. Therefore, educating the community about personal data protection, particularly for the data management team in Duri Kepa Village, is seen as a solution that is expected to enhance understanding and awareness of the importance of information security. This community service activity is perceived to provide significant benefits to the public, one of which is to offer a deeper understanding of data protection, applying knowledge and technology in a tangible contribution to society. Early efforts to protect personal data from cybercrime related to data theft involve understanding the threats to personal data and knowing the preventive measures. The need for this presentation and training is realized through Community Service (PkM) activities conducted by lecturers and students as part of the Tri Dharma of Higher Education